Classifying training drills based on movement demands in Australian football - Loader, J.; Montgomery, P. G.; Williams, M. D.; Lorenzen, C.; Kemp, J. G. (International Journal of Sports Science and Coaching, 2012)
Time-motion data was used to classify a selection of training drills. Ten midfielders (age=23.8±1.8yr; height=183.9±3.8cm; mass=83.2±5.0 kg) from an Australian Football League team participated in 17 training drills and four quarters of an official competitive match. Heart rate and time-motion data were collected using Global Positioning and Heart Rate Systems. Cluster analysis of mean distance travelled in the seven velocity zones identified three clusters: 1) game-specific conditioning; 2) skill refining/moderate intensity dominant; and 3) skill refining/low intensity dominant. Differences between the three clusters in distance travelled at the speed zones were confirmed using one-way ANOVA. Differences between clusters were also assessed for number of efforts in velocity zones and percentage time in heart rate zones. When compared to drills with a focus on skill refining or performed on a reduced playing area, drills utilising the entire playing field better replicated the movement characteristics of competitive game play.